Is EU Support to Malawi Agriculture Effective? - Wouter Zant (Tinbergen Institute, 2012)
We measure the impact of the Farmers Income Diversification Program (FIDP), an EU funded program implemented in Malawi from late 2005 onwards, aiming at increasing agricultural productivity, diversification, value addition, commercialization and trade of subsistence farmers. The geographical spread of the implementation of FIDP is exploited to identify its impact. Computations are based on annual data by Extension Planning Area, 198 in total, fully covering Malawi, for the period 2003-04 to 2009-10. The estimations support a statistically significant impact of FIDP on agricultural productivity, with increases reaching 20% to 24% relative to base period levels, with a lag of at least one year after the start of the program and increasing over the years. Evidence on diversification of crop income is less strong but still suggests increases ranging from 5% to 10%. Results are robust for instrumental variables, synthetic controls, clustering of standard errors and inclusion of additional covariates.
urn:NBN:nl:ui:31-1871/38481
Keywords: F35; O13; O55; Q11; Q13; 330; agricultural policy; impact evaluation; subsistence farming; Malawi; Africa; Entwicklungshilfe; EU-Staaten; Landwirtschaftliche Entwicklung; Subsistenzwirtschaft; Malawi